The relationship of Takaful agents’ Islamic ethical behaviour towards customers’ satisfaction, trust and commitment: a preliminary analysis - Che Mohd Salleh, Marhanum; Abdullah, Nurdianawati Irwani; Razali, Siti Salwani (2013)
Takaful agents have become among the important distribution channels in Takaful industry. Besides selling Takaful products, the agents must practice Islamic ethical behaviour in dealing with customers. This research seeks to investigate the relationship between Takaful agents’ Islamic ethical behaviour and customers’ satisfaction, trust and commitment. As there are limited studies conducted in this area, this research provides a preliminary analysis with 30 Takaful customers. Data were collected through survey research design using questionnaire as the research instrument. The data gathered is analyzed using SPSS WIN 19 for both descriptive statistics (frequency, percentage, mean and standard deviation) and correlation coefficient (Pearson r). Results indicate that the agents’ Islamic ethical behaviour have significantly relationship with customers’ satisfaction, trust and commitment. However, there are different in terms relationship strength. Besides that, majority of respondents were slightly agreed about the practicing of Islamic ethics among the agents. In this instance, Takaful operators need to play their role in guiding and encouraging their agents to practice the Islamic ethical behaviour in marketing Takaful products. It is important to differentiate the marketing practices of Takaful from conventional insurance in order to gain publics’ satisfaction, trust, and commitment.